Significant theories in supervision process: a study in Malaysian context - Ghazali, Nor Mazlina; Wan Jaafar, Wan Marzuki; Ahmad Tarmizi, Rohani; Mohd Noah, Sidek (Elsevier, 2015)
The purposes of this study were (i) to investigate the significance of theoretical orientation amongst supervisee (counselling trainee) and (ii) to investigate the significance of theoretical orientation amongst supervisor (lecturer) during supervision process. 120 supervisees (counselling trainees) and 18 supervisors (lecturer) from four public universities in Malaysia were selected as respondents through stratified random sampling. The Selective Theory Sorter (STS) has been used to measure significant theory applied by supervisor and supervisee (Duane and Kimberly, 2006). Means, standard deviations, and percentage were reported in the study. It is essential to identify the theoretical orientation in order to determine the intervention.